THE CCB TREATMENT OF SIXTEEN INDONESIAN WOOD SPECIES AGAINST MARINE BORERS - Muslich, Mohammad (Indonesian Journal of Forestry Research, 2006)
This  study was conducted to provide basic information  on the treatment of some wood species using a copper bichromated boron (CCB).  The specimens  were treated with CCB for 2 hours  in a 150 psi of full cell process.  The treated and untreated wood samples were tested against marine borers for 4, 8 and 12  months.  The results indicated that full cell process with CCB were able  to prevent marine borers  attack. Untreated  wood  specimens were susceptible to marine borers attack, except Iara (Metrosiderospetiolata Kds.) and kandole  (Diploknema oligomera HJ.L.).  The attacking borers  are Martesia striata Linn of the Pholadidae   family, Teredo bartschi Clapp.,  Dicyathifer manni Wright and Bankia  cieba Clench.  of the Teredinidae family. However, crustaceans   were found clinging to the wood specimens when they were taken from the sea. These crustaceans belongs to Sphaeromatidae family.